The Effect Of Curing Time On Electrical Resistivity, Mechanical Characteristics And Microstructure Behavior Of Graphene Conductive Ink - Salim, Mohd Azli; Masripan, Nor Azmmi; Md. Saad, Adzni; Ab Wahid, Ameeruz Kamal; Ali, Murni; Al-Mola, Mohammed Hussin A. (Penerbit UniMAP, 2021)
Nowadays graphene conductive ink (CI) are expected to be widely used for various automotive safety electronic equipment in the future. Graphene has a potential advantage such as high electrical conductivity and thermal conductivity and can be applied to electronic circuits in vehicles especially for driver health monitoring systems. To ensure optimal conductivity, graphene need to go through a curing process to minimize porosity between particles and create a smooth conductive track. The effect of curing time on electrical, mechanical, and microstructural properties was investigated. Five samples at 20 wt.% filler loading with curing times varying from 10-50 minutes with each sample interval of 10 minutes was executed using doctor-blading printing method before analysis. Then, the analysis is done by using four-point probe to measure resistance, followed by nanoindentation and scanning electron microscope (SEM) to study elasticity and observe microstructure behaviour respectively with respect to temperature. Sample of 30 minutes curing time gives the lowest result, 24.9046 Ω.cm for volume of resistivity. The sample also has excellent mechanical properties, with high Young's modulus and low hardness, 8.59 GPa and 7.59 MPa respectively. Stretchable conductive ink (SCI) in vehicle electronic equipment with low resistance and high elasticity can monitor the driver's health more refectively because it can be stretched to fit the shape of the human body. It also has good conductivity for measuring human pulse and muscle movement.